Wykładnia twórcza a tzw. wykładnia prawotwórcza - Potrzeszcz, Jadwiga (PRAWO i WIĘŹ, 2025)
The goal of the present paper is the attempt to identify and distinguish between the phenomena of creative interpretation and so-called law-making interpretation. The starting point is the assumption that the concepts of creative interpretation and so-called law-making interpretation are not identical, although they are frequently used interchangeably in legal doctrine and judicial practice. Recognition of the need to distinguish between creative interpretation and the phenomenon of so-called law-making interpretation is inextricably related to the thesis adopted and argued in this paper, according to which creative interpretation is an acceptable, frequently required and indispensable form of interpretation, whereas so-called law-making interpretation in its essence is by no means interpretation, but occurs in legal practice and is a phenomenon that must not be accepted under any circumstances. In principle, the prohibition of legal interpretation is widely recognized in doctrine and judicial practice. Although such a prohibition applies to all entities interpreting the law, it is particularly relevant to the judiciary in the context of the principle of the separation of powers. An interpreter is not allowed to create legal norms in a subjective and arbitrary manner, because such an act is no longer interpretation but enters the realm of law-making. The issue at stake is not law-making understood as the creation of legal provisions, but law-making understood as the creation of legal norms that have not been previously codified by a rational legislator in legal provisions.